Mobilidade das ocupações agrícolas no mercado de trabalho formal do Brasil - Dias, Thyena Karen Magalhães (2025)
The Brazilian agricultural labor market has undergone significant transformations over the past decades, driven by agricultural modernization and its consequences. In this context, this thesis investigates the occupational mobility of Brazilian agricultural workers and analyzes income differentials between those who remained in agricultural occupations and those who transitioned to non-agricultural activities. The study uses microdata from the Annual Social Information Report (RAIS) covering the period from 2003 to 2019, along with econometric methods such as the Logit model, Unconditional Quantile Regression (RIF), and the RIF decomposition proposed by Firpo, Fortin, and Lemieux (2007; 2009). The results indicate that factors such as initial income, firm size, disability status, and public sector employment increase occupational mobility, whereas age, male gender, white race, job tenure, and working hours tend to reduce it. Regionally, the North, Center-West, and South show higher mobility compared to the Southeast, while the Northeast exhibits lower propensity for occupational transition. Immediate mobility is associated with higher earnings at the upper percentiles of the income distribution, while non-immediate mobility benefits the lower percentiles but results in lower earnings at the top percentiles. Additionally, experience, gender, and education are positively associated with income. Regarding income differentials among workers, mobility has varying effects depending on its type, with the unexplained component playing a predominant role—highlighting the importance of education in reducing wage inequality.